Neuromuscular Training and Adaptations in Youth Athletes - David G. Behm (Frontiers Research Topics, 2018)
The Frontiers Research Topic entitled "Neuromuscular Training and Adaptations in Youth Athletes" contains one editorial and 22 articles in the form of original work, narrative and systematic reviews and meta-analyses. From a performance and health-related standpoint, neuromuscular training stimulates young athletes' physical development and it builds a strong foundation for later success as an elite athlete. The 22 articles provide current scientific knowledge on the effectiveness of neuromuscular training in young athletes.